THE APPLICATION OF MODERN LEGAL POSITIVISM TO THE PRINCIPLE OF LEGAL CERTAINTY IN CERTIFICATE OF PROPRIETARY RIGHTS TO LAND - I Gusti Agung Ngurah Agung (Awang Long Law Review, 2022)
Certificate of ownership of land is a strong and complete proof for everyone whose names are listed and listed in the certificate of ownership of the land. However, in reality the SHM on the land can be canceled at any time as stipulated in Article 32 of Government Regulation Number 24 of 1997 concerning Land Registration, whereas in Article 20 Paragraph (1) of Law Number 5 of 1960 concerning Agrarian Principles it is stated that property rights, namely as hereditary rights, the strongest and fullest. Thus the legal certainty of SHM on land is not absolute because the SHM on the land can be canceled at any time. It is necessary to renew the principle of negative publications with positive tendencies that do not have a strong rationale for legal certainty, justice and expediency. The problem is, how is the legal certainty of the current Land Ownership Certificate which can then be canceled after a period of five years has passed since the issuance of the certificate of title to the land through a modern legal positivism approach? and what is the solution to the cancellation of land title certificates based on the conditions of das sein and das sollen?. The research method, in this dissertation research used normative juridical research methods. The conclusion of the study, the land registration system in Indonesia adheres to a negative publication system with a positive tendency. This system basically does not provide legal certainty, let alone good legal protection for certificate holders.